1971
DOI: 10.2134/agronj1971.00021962006300010043x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Rates and Plant Spacing on Sunflower Seed Yields and Other Characteristics1

Abstract: Field experiments were conducted to determine effects of nitrogen and plant spacing on sunflower (Helianthus annuus L.). Nitrogen rates were 0, 56, 112, and 168 kg/ ha, and plants were spaced 15, 30, and 46 cm apart within rows 1.1 m wide. Nitrogen at 56 kg/ha increased seed yield, grams of seed per head, seed size, and head diameter 653 kg/ha, 17.7 g, 1.9 g/200, and 2.2 cm, respectively, as compared to nontreated plots. Plant height was increased 11 cm and stem diameter 4 mm by 56 kgN/ha. No further increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

1982
1982
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 0 publications
1
19
0
1
Order By: Relevance
“…In North Dakota, increasing sunflower population from 36 000 to 72 000 plants /ha significantly increased seed yield from 2 258 to 3190 kg/ha, oil yield from 1 046 to 1500 kg/ha, even though flower diameter was (Zubriski & Zimmerman, 1974). Similarly, Massey (1971) reported an increase in seed yield from 1667 to 2 839 kg/ha by increasing the plant population from 20 000 to 60 000 plants/ha. However, in Minnesota an increase in plant population from 37 000 to 86 000 plants/ha increased yield at only one of two locations (Robinson, 1973).…”
Section: Source Of Variationmentioning
confidence: 95%
See 1 more Smart Citation
“…In North Dakota, increasing sunflower population from 36 000 to 72 000 plants /ha significantly increased seed yield from 2 258 to 3190 kg/ha, oil yield from 1 046 to 1500 kg/ha, even though flower diameter was (Zubriski & Zimmerman, 1974). Similarly, Massey (1971) reported an increase in seed yield from 1667 to 2 839 kg/ha by increasing the plant population from 20 000 to 60 000 plants/ha. However, in Minnesota an increase in plant population from 37 000 to 86 000 plants/ha increased yield at only one of two locations (Robinson, 1973).…”
Section: Source Of Variationmentioning
confidence: 95%
“…Sunflower (Helianthus annuus L.) is a major source of high quality vegetable oil and is also grown for confectionary and birdfood markets (Johnston et al, 2002;Massey, 1971;Swallers & Fick, 1973;Zubriski & Zimmerman, 1974). Sunflower is cultivated in many semi-arid regions of the world from Argentina to Canada and from central Africa into Russia (Robbelen & Downey, 1989;Andrade, 1995;Angadi & Entz, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Head diameter was 20.7 and 20.6 cm for the N rates of 120 and 160 kg N/ha, respectively, while it was 18.48 cm for the check treatment. Some research data (Massey 1970, Hussein et al 1980) have also shown that fertilizer nitrogen increased head diameter of the sunflower. 1000 seed weight is commonly a major determinant of sunflower yield.…”
Section: Yield Componentsmentioning
confidence: 90%
“…Beskikbare plaaslike inligting oor die bemesting van sonneblomme is dikwels verouderd weens verouderde kultivars wat gebruik is, of i,s nie verteenwoordigend van die sonneblomproduserende; gebiede in Suid-Afrika nie (Du Toit, 1974;Bazelet, Dijkhuis & Eisenberg, 1981;Blamey & Chapman, 1981). Oorsese literatuur dui daarop dat sonneblomme minstens 50 kg N ha-I benodig in die vorm van bemesting (Massey, 1971;Zubriski & Zimmerman, 1974;Zubriski, Deibert & Schneider, 1979;Mathers & Stewart, 1982;Narwal & Malik, 1985). Tans word van 22 tot 87 kg N ha -I vir sonneblomme in Suid-Afrika aanbeveel vir opbrengspotensiale van 1 000 tot 3 000 kg ha -\ (Misstofvereniging, 1987).…”
Section: Inleidingunclassified